The Effect of Short-Form Videos on Impulse Buying: The Mediating Role of Emotional Arousal and the Moderating Role of Fear of Missing Out (FOMO) - Diana, Mila Irian; Hadi Raharjo, Raden Johnny (LPPM Universitas Jambi, 2026)
The rise of social commerce platforms that integrate short-form video creates a more engaging shopping experience, which can influence consumer purchasing behavior. This study aims to analyze the influence of short-form video on impulse buying, with emotional arousal as a mediator and fear of missing out (FOMO) as a moderator, among Generation Z TikTok users in Indonesia. The study employs a quantitative approach using a survey method with 140 respondents and is analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that short-form videos have a positive and significant effect on emotional arousal with a coefficient of 0.712 and a p-value of 0.000, emotional arousal has a positive and significant effect on impulse buying with a coefficient of 0.156 and a p-value of 0.021, and emotional arousal mediates the effect of short-form videos on impulse buying with a coefficient of 0.111 and a p-value of 0.020. Furthermore, FOMO was found to positively moderate the relationship between emotional arousal and impulse buying with a coefficient of 0.082 and a p-value of 0.043. These findings indicate that emotional responses and FOMO play a significant role in explaining impulsive buying behavior on short-form video-based social commerce platforms.